Does firm’s higher innovation potential lead to its superior financial performance? Case of CEE countries - Bistrova, Julia; Lace, Natalja; Tamošiūnienė, Rima; Kozlovskis, Konstatins (Technological and Economic Development of Economy, 2017)
Innovation is one of the most commonly used word in the business and academic world. Naturally the firms are willing to innovate to leverage on future profits and growth generated by the new products and supported by temporary monopolistic positions on the market. However, the question is about how much the companies should invest to record higher profitability. The authors tried to answer this question analyzing the companies within the Central and Eastern European region taking intangible assets as innovation proxy. It was concluded that the companies having higher investments in the intangible assets are able to generate higher margins. However, positive effect of possibly higher innovation potential is seen only if investments in intangibles are substantial, i.e. over 10%.